Deterring violent non-state actors: dilemmas and implications. Issue 1 (11th June 2019) - Elbahy, Raghda
Abstract : Purpose: This paper aims to address the limitations of classical deterrence theory in dealing with violent non-state actors (VNSAs). Design/methodology/approach: The study uses qualitative methods. Findings: It suggests that two measures must be applied; the first one is to rephrase the assumptions of the theory towards a broader definition. The second one is to theorize certain approaches for deterring VNSAs which shall remain a key component in, but not the cornerstone of, national security strategies. Originality/value: In the aftermath of 9/11 attacks and US war on terrorism, the need arose to "revisit" the "Deterrence Theory" to address several changes such as rogue states, cyber threats and VNSAs, especially after the end of the Cold War, when the theory was originally developed. The recent research on VNSAs relates to the fourth wave of deterrence, which highlights its proper role in a new security environment.